THE FORMATION AND NATURE OF POLITICAL CULTURE IN PRESENT-DAY KYRGYZSTAN - TOROGELDIEVA, Baktykhan (CENTRAL ASIA AND THE CAUCASUS, 2009)
Present-day Kyrgyzstan is going through a rather difficult period in its development. The transformations in culture, the economy, and the state-political structure have affected all aspects of Kyrgyz society’s life across the board, whereby these processes are often very excruciating and accompanied by severe social upheavals. A fundamental element of the dynamics of the social transformations aimed at establishing market relations in Kyrgyzstan is the constant change in those values on which the nation’s people, who have grown up in a traditional and then Soviet society, are building their world outlook. This has given rise to a legitimate interest in searching for rational explanations to the processes occurring in the country’s political culture. In this article we will try to analyze the main factors influencing the formation and nature of political culture in Kyrgyzstan. Political culture is a structure that becomes increasingly richer and more complicated. The problem of forming and advancing a different type of political culture that is better suited to the democratic trend in Kyrgyzstan’s development is extremely pertinent for the Kyrgyz people. This requires its re-examination from the viewpoint of the new democratic values taking shape in the republic. It is particularly important in current conditions when globalization and democratization are drawing new and nontraditional strata of the population into political life. Political culture is quite a stable phenomenon. It, just as culture in general, is a system that is least affected by change. Its main function is to reproduce an image and on its basis guarantee the continuity of society’s political life and support of society as a systemic whole. At the same time, society cannot adapt to the changing conditions and fundamental transformations in political life and the entire social system without profound metamorphosis of political culture. So in each specific situation it is a unique synthesis of its formation, functioning, and development, whereby it can be regarded as a dynamic rather than petrified system.Political culture undergoes the most significant changes during transition periods of revolutionary changes or reform in society and the state, when certain value and ideological shifts occur in the mass consciousness generated by an abrupt change in the customary political practices. At times of radical social change and a breakdown in the former political system, new images can be incorporated into the system of political cultures. However, this process is complicated and contradictory.